Tantangan Mencegah Eigenrichting dalam Bingkai Komunikasi Sosial - Alen Manggola (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study is to see the description of vigilante or eigenrichting in social communication. The method in this study uses a quantitative approach, with explanatory research methods. The results of the study that this act of vigilantism (Eigenrichting) is then in the national legal order contrary to the principle of presumption of innocence. So a person should not be convicted or not without going through a legal process, because there is a possibility that someone is innocent but becomes a victim of vigilantism. The conclusion of the research shows that vigilante will respond to situations that are full of undirected ambition into a spurring attitude, that something needs careful consideration before acting, because it does not rule out the possibility that it will result in greater losses. Keywords: Eigenrichting, Social Communication.